Integrating paleopathology and paleoecology to unravel the lifestyle of the Pleistocene sloth Nothrotherium maquinense - de S. Barbosa, Fernando H.; da Silva, Rafael Costa; Alves-Silva, Laís; Liparini, Alexandre; de Araújo-Júnior, Hermínio I. (Journal of mammalian evolution, 2024)
Nothrotherium maquinense , an extinct sloth species that existed alongside other megafauna during the Pleistocene, has been a subject of intense debate regarding various aspects of its life. This study integrates an examination of specific forearm bone fracture (paleopathology) with forelimb functional indices (paleoecology) in N. maquinense in order to infer its likely mode of locomotion and substrate preferences. Our findings provide compelling evidence suggesting that N. maquinense possessed climbing abilities and likely had a semi-arboreal lifestyle. Additionally, we report the first occurrence of calcium pyrophosphate deposition disease (CPPD) in this species, indicating that this type of arthritic condition was present in this sloth.